Specialized Dietary Fibers Alter Microbiome Composition & Promote Fermentative Metabolism in the Lower Gastrointestinal Tract of Healthy Adult Cats (P20-045-19). (13th June 2019) - Wernimont, Susan; Fritsch, Dale; Jackson, Matthew; Badri, Dayakar; Cochrane, Chun-Yen; Gross, Kathy
Abstract: Objectives: The feline gastrointestinal (GI) microbiome is capable of fermenting fibers. We evaluated specialized dietary plant fibers on feline GI microbiome composition & metabolism. Methods: 46 healthy adult cats were fed control food (CF) for 4 wks & test food (TF) for 8 wks (CF: 4129 kcal/kg, 1.6 g total dietary fiber, TDF; 0.7 g soluble fiber, SF; & 0.9 g insoluble fiber, INSF, per 100 kcal; TF: 4010 kcal/kg, 3.2 g TDF, 0.3 g SF, 2.9 g INSF per 100 kcal). All foods were complete balanced dry products & met 2017 AAFCO maintenance guidelines. CF fiber sources: cracked pearled barley, corn, dried beet pulp, fructooligosaccharides (FOS) & psyllium seed husk; TF: corn, ground pecan shells, cracked pearled barley, whole grain oats, dried beet pulp, pea fiber, flaxseed, dried citrus pulp, pumpkin, cranberry pomace, FOS & psyllium seed husk. Feces were collected after 4 wks of CF & after 4 & 8 wks of TF, cleaned of litter, homogenized, & frozen at −70C within 1 hour of defecation. Cats had free access to water, natural daylight & enrichment from toys, other cats & people. The study was reviewed & approved by the Institutional Animal Care & Use Committee, Hill's Pet Nutrition, Inc. Fecal microbiome 16 s rRNA sequencing was performed using Illumina MiSeq & processed by Mothur. Predicted microbial functions were determined by PICRUSt & analyzed using PERMANOVA. The copy number corrected OTU counts were analyzed using negative binomial mixed models. Fecal short chain fatty acids (SCFA) were analyzed using liquid-liquid extraction & gas chromatography with flame ionization detection. Results significant at P < 0.05 are reported. Results: At 4 & 8 wks, TF significantly increased acetic & propionic acids, decreased isobutyric, 2-methylbutyric, & isovaleric acids. The genera Peptococcus, Succinivibrio & Enterococcus were significantly decreased vs. CF at 4 & 8 wks while Blautia, Bacteroides, & Turicibacter were significantly increased vs. CF at 4 & 8 wks. Predicted microbial functions representing arginine, benzoate, butyrate, phenylalanine, propionate, tryptophan & tyrosine metabolic pathways were significantly different from CF at 4 wks. Conclusions: TF shifts feline GI microbiome composition & metabolism toward saccharolytic fermentation & decreases putrefactive metabolites, characteristics which may benefit feline GI health. Funding Sources: This study was funded by Hill's Pet Nutrition, Inc.